2015
DOI: 10.1111/febs.13231
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin I, a molecular target for steroid hormone signaling controlling the maturation of sexual behavior in an insect

Abstract: As in vertebrates, the insect steroid hormones, especially 20-hydroxyecdysone (20E), initiate and regulate sexual behavior by acting on the central nervous system. This 20E action is, in part, triggered by transcriptional events mediated through the binding of 20E to a heterodimer comprising the ecdysone receptor (EcR) and ultraspiracle (USP). However, to date, our knowledge about this genomic steroid pathway remains incomplete. In moths, males detect female sex pheromones, eliciting stereotyped sexual behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Over these last years, growing evidence has accumulated about the involvement of 20E in the maturation of sex pheromone responses in A. ipsilon male. Indeed, it has been showed that 20E is necessary to enhance high sensitivity to sex pheromone in males during their sexual development and that this positive effect is at least in part transduced through the activation of EcR/USPdependent signalling in ALs [37], ultimately engendering the upregulation of neural plasticity-related proteins such as the synaptotagmins [38]. It is interesting to emphasise that the behavioural changes resulting from AiHR38 depletion are similar to those induced by the pharmacological inactivation of 20E/EcR/USP complex [37] or RNAi-mediated EcR silencing [38].…”
Section: The Concomitant Increased Al and Sag Aihr38 Expressions Contmentioning
confidence: 99%
See 2 more Smart Citations
“…Over these last years, growing evidence has accumulated about the involvement of 20E in the maturation of sex pheromone responses in A. ipsilon male. Indeed, it has been showed that 20E is necessary to enhance high sensitivity to sex pheromone in males during their sexual development and that this positive effect is at least in part transduced through the activation of EcR/USPdependent signalling in ALs [37], ultimately engendering the upregulation of neural plasticity-related proteins such as the synaptotagmins [38]. It is interesting to emphasise that the behavioural changes resulting from AiHR38 depletion are similar to those induced by the pharmacological inactivation of 20E/EcR/USP complex [37] or RNAi-mediated EcR silencing [38].…”
Section: The Concomitant Increased Al and Sag Aihr38 Expressions Contmentioning
confidence: 99%
“…Indeed, it has been showed that 20E is necessary to enhance high sensitivity to sex pheromone in males during their sexual development and that this positive effect is at least in part transduced through the activation of EcR/USPdependent signalling in ALs [37], ultimately engendering the upregulation of neural plasticity-related proteins such as the synaptotagmins [38]. It is interesting to emphasise that the behavioural changes resulting from AiHR38 depletion are similar to those induced by the pharmacological inactivation of 20E/EcR/USP complex [37] or RNAi-mediated EcR silencing [38]. It is also noteworthy that the age-related expression dynamic of AL AiHR38 is positively correlated with the agedependent increase in the levels of circulating 20E and of expression of EcR and USP in ALs [37].…”
Section: The Concomitant Increased Al and Sag Aihr38 Expressions Contmentioning
confidence: 99%
See 1 more Smart Citation
“…The dsRNA production and injection conditions were established by following the protocol used for the silencing of a Gprotein-coupled dopamine/ecdysteroid receptor (AipsDopEcR) and the ecdysone receptor (AiEcR) in A. ipsilon (Abrieux et al, 2013;Bozzolan et al, 2015). The dsRNAs designed against AiERR (425 bp) and bacterial LacZ (372 bp) were produced with a MEGAscriptV R T7 High Yield Transcription Kit (Ambion) according to the manufacturer's instructions.…”
Section: Rna Interference Experimentsmentioning
confidence: 99%
“…In addition, functional studies of genes playing distinct roles during development and adult life could be challenging since the loss of function of these GOI generally leads to lethal phenotype 22 . As shown in studies addressing the characterization of hormonal pathways for example, the same set of genes could be involved in both developmental processes and regulation of physiological state in an age-dependent manner 23,24 . In such scenario, the temperature dependent UAS/Gal80 25 or other inducible systems 21 can be used in model species.…”
Section: Application Of Modified Yeast Expressing Dsrna In Reverse Gementioning
confidence: 99%